MAKNA KETERSEDIAAN TRANS SARBAGITA JALUR DENPASAR-GWK BAGI PARIWISATA BALI - Saragih, Ester Venni Olita; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 3 No 2 (2015): VOL 3, NO 2 (2015): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2015)
A BSTRACT This study is about The Meaning of Availability Trans Sarbagita on Denpasar-GWK’s Track for Bali’s Tourism. The purpose of this study was to determine the availability of public transportation issued by the government , namely trans Sarbagita in serving the local community in performing its activities and also traveled to minimize the level of congestion is becoming a major problem especially in Bali Denpasar path - pedestal which is the main route across Bali tourism . In this study data using for translation of information about the problem under study, information obtained from the Head of the Department of Transportation Sarbagita part of Denpasar. Information obtained through observation, questionnaires, interviews and in-depth study of literature. The technique used is the determination of the informant to informant while Purpose Sampling for determination of respondents conducted by meode quota sampling. The method used in this research is the method of analysis is descriptive and qualitative analysis method that is reinforced by the results of an open questionnaire, observation, and interviews that can support this conclusion panelitian. Based on the results, the following results; traffic jams that occur in Bali due to lack of public transport services, people prefer to use private transport. Trans Sarbagita presence that aims to serve the community and reduce congestion, the impact on sustainability and tourism activities in Bali.
Keywords: Meaning, Availability, Public Transportation, Tourism